Posterior Segment Toxicity after Gemcitabine and Docetaxel Chemotherapy. Issue 5 (May 2015) - Kord Valeshabad, Ali; Mieler, William F.; Setlur, Vikram; Thomas, Merina; Shahidi, Mahnaz
ABSTRACT Purpose To report outer retinal disruption and uveal effusion after gemcitabine and docetaxel combination therapy. Case Report A 78-year-old woman presented with blurry vision after two cycles of gemcitabine and docetaxel combination chemotherapy for stage IV sarcoma. At presentation, visual acuity was finger counting and 20/25 in the right and left eyes, respectively. Slit-lamp examination and B-scan ultrasonography revealed severe uveal effusion in the right eye and choroidal folds in the left eye. Spectral domain optical coherence tomography showed disruption of photoreceptor inner segment ellipsoid band in the right eye. The patient was monitored weekly with ophthalmic examination and B-scan ultrasonography, while continuing with gemcitabine monotherapy. At 8 weeks follow-up, uveal effusion improved considerably and visual acuity was 20/40 and 20/20 in the right and left eyes, respectively. Conclusions Uveal effusion and outer retinal disruption were reported after gemcitabine and docetaxel chemotherapy. Early detection and close ophthalmic monitoring may allow concurrent cancer treatment and prevention of possible chemotherapy-induced ocular side effects.